(untitled) (American Journal of Interdisciplinary Research and Development, 2025)
Foreign language proficiency is becoming increasingly important in the field of finance due to the global nature of the industry. This article explores the significance of foreign language teaching methodology tailored specifically for finance professionals. It delves into the challenges faced in teaching finance-related language skills and highlights effective strategies and methodologies that can enhance language learning in this specialized domain.